NEAR FAULT VELOCITY PULSE ESTIMATION: THE CEPHALONIA FEB. 3, 2014 EARTHQUAKE (M6.0) - Theodoulidis, N.; Grendas, I. (Bulletin of the Geological Society of Greece, 2016)
Near fault ground motions can be significantly different than those further away from the seismic source. Within the near fault zone ground motions are drastically influenced by the rupture mechanism, the direction of rupture propagation relative to the site and possible permanent displacement related to the fault slip. During the past two decades several sophisticated theoretical or/and empirical methods have been proposed to simulate near fault motion requiring input parameters that hardly can be provided with accuracy, leading thus to extended parametric studies and uncertainties. In this paper, a simple but effective analytical model that mathematically represents near fault ground motions (Mavroeidis and Papageorgiou, 2003) is applied and tested in the case of Cephalonia, Feb. 3, 2014 earthquake (Μ6.0). Its validity and reliability are examined and an effort to distinguish source and possible site effects is attempted for the town of Lixouri (LXR1 accelerograph) where the highest damage levels was observed.